Identification of glycosylated flavonoids as new physiological ligands of the hazel allergen Cor a 1: Complex structures reveal different binding orientation and specificity of mono- and disaccharide derivatives - Julian M. Hendrich; Hatice Kara; Kristian Schweimer; Thessa P. Jacob; Maike Schneider; Susanne Baldermann; Birgitta M. Wöhrl (Food Chemistry: X, 2025)
The global production of hazelnuts is rising, but hazelnut allergies remain common and severe. The PR-10-like allergen Cor a 1, found in hazel pollen and nuts, consists of different isoallergens with over 67 % sequence identity. Cor a 1 binds plant secondary metabolites like the diglycosylated flavonoid Q3O-(Glc)-Gal. Understanding the ligand binding of Cor a 1 isoallergens is crucial to understand their physiological and allergenic properties.We identified physiological mono- and diglycosylated flavonoids from hazel pollen by UHPLC/QTOF-MS and NMR spectroscopy and investigated their binding to Cor a 1 isoallergens by NMR HSQC experiments and ITC titrations. Screening analyses revealed different binding properties of isoallergens. Whereas the isoallergen Cor a 1.0501 bound only monoglycosylated flavonoids, Cor a 1.0401 also bound diglycosylated flavonoids. Protein/ligand complex structures based on NMR NOESY and computational docking experiments revealed different orientations of mono- vs. diglycosylated flavonoids in the amphiphilic pocket and specific binding of disaccharide derivatives.